Developing Interactive Learning Media of Worksheets based on Geogebra Classroom - Badriyanto, Badriyanto; Qohar, Abd (Universitas PGRI Madiun, 2022)
Technological developments open up opportunities for education to continue to develop, especially during the COVID-19 pandemic, optimal use of technology is necessary. The need for adjustments to the LKPD (student worksheet) which is a learning medium and is an important component in teaching and learning activities to suit the current situation. The results of the observations found that there was no adjustment to this matter. This study aims to develop digital worksheets based on the geogebra classroom on set material, especially set operations. This study uses the DDD-E method with the stages of decide, design, develop and evaluate. The subjects of this research were 32 students of class 7D UM Laboratory Junior High School. The trial process is carried out during class. The digital LKPD (student worksheet) based on the geogebra classroom for set material, especially on set operations, has been developed. The developed learning media has been validated and obtained a media validation score of 3.49 and material validation 3.45 which indicates that this media is valid. The results of the practicality test obtained from the questionnaire distributed to students got a score of 3.24. As for the effectiveness of getting a score of 3.25 and help 78% of all students reach a KKM. This shows that the media developed is both practical and effective. Based on the results of validation, effectiveness and practicality, the developed digital worksheet based on the geogebra classroom can be used to study the topic of set operations. 45 which indicates that this media is valid. The results of the practicality test obtained from the questionnaire distributed to students got a score of 3.24. As for the effectiveness of getting a score of 3.25 and help 78% of all students reach a KKM. This shows that the media developed is both practical and effective. Based on the results of validation, effectiveness and practicality, the developed digital worksheet based on the geogebra classroom can be used to study the topic of set operations. 45 which indicates that this media is valid. The results of the practicality test obtained from the questionnaire distributed to students got a score of 3.24. As for the effectiveness of getting a score of 3.25 and help 78% of all students reach a KKM. This shows that the media developed is both practical and effective. Based on the results of validation, effectiveness and practicality, the developed digital worksheet based on the geogebra classroom can be used to study the topic of set operations.